Les piles intra muros de l’aqueduc du Gier, rue Roger-Radisson à Lyon - Éric Bertrand (Gallia)
Road works carried out in 2018 on the site of the arches of the Gier aqueduct, on rue Roger-Radisson in Lyon, required the implementation of an emergency archaeological operation. The excavations conducted around the last pier (no. 10), partially preserved in the foundations of a house, revealed the unusual design of this structure. G. M. Delorme’s architectural survey, carried out in the 18th century, shows the pier before its last alteration: already incomplete, its quarter-round facings clearly initiate a 90° reorientation of the aqueduct towards the south. The quality of Delorme’s work on the aqueduct as a whole and the state of preservation of the construction in his time confirmed this analysis of the structure’s route, potentially restricted by the presence of the Roman circus.The excavation of a plot of land to the east of the last pier confirms that the aqueduct did not develop in a linear fashion. However, the excavation of the aqueduct’s structures shows inaccuracies in Delorme’s survey. It also led to the discovery of a short linear wall attached to the pier by its continuous opus reticulatum, which diverges in its orientation from the course of the aqueduct. This complex and unusual architectural layout for the aqueduct has prompted new hypotheses regarding its integration into the ancient urban fabric. For example, the bevelling of the pier found in the 18th century and of the buried structures excavated in 2018, could indicate the existence of a ramp designed to distribute water from the Gier (partially or totally) at local scale. However, the excavation area is not large enough to allow a complete analysis of the structure and to validate the fact that the aqueduct really ended its course at pier no. 10.The stratigraphic context of the excavation and the ceramic material associated with the construction tend to confirm that the aqueduct is not an early construction and would not have been built before the 2nd century CE.